Effect of brain acetylcholine depletion on bicuculline-induced cardiovascular and locomotor responses - GÜLHAN, REZZAN (GORDON BREACH SCI PUBL LTD, 1997)
Both GABAergic and cholinergic systems are involved in central cardiovascular regulation. Previous studies have shown that GABA(A) receptor antagonists cause increases in blood pressure, heart rate and locomotor activity. In this study, we examined the role of the depletion of brain acetylcholine on the cardiovascular responses and locomotor activity induced by bicuculline methiodide in conscious Sprague-Dawley rats. The doses of 0.3 and 0.5 nmol of intracerebroventricular bicuculline methiodide produced increases in blood pressure, heart rate and locomotor activity. The dose of 18 nmol of hemicholinium-3 to deplete brain acetylcholine was given intracerebroventricularly one hour prior to bicuculline methiodide. The presser responses to bicuculline methiodide in animals pretreated with the hemicholinium-3 were higher than those seen in saline-pretreated groups, bur locomotor activity and heart rate responses to bicuculline methiodide remained unchanged in hemicholinium-3 pretreatment group. On the other hand, high dose of bicuculline methiodide (0.5 nmol) caused convulsions in some animals pretreated with hemicholinium-3 whereas bicuculline methiodide, alone, did nor cause any seizure activity. In conclusion, it seems likely that endogenous brain acetylcholine could be a modulator of GABA(A) receptor-mediated blood pressure control.
Keywords: GABA(A) receptor; acetylcholine; cardiovascular function; locomotor activity; BASAL FOREBRAIN; POSTERIOR HYPOTHALAMUS; GABAERGIC NEURONS; GABA ANTAGONISTS; BLOOD-PRESSURE; RAT; RECEPTORS; PHYSOSTIGMINE; HYPERTENSION; HIPPOCAMPUS